MAIT cells in sterile and non-sterile inflammation - Howson, L (2017)
Mucosal-associated invariant T (MAIT) cells are an innate-like T cell subset that recognize bacteria-derived metabolites presented on MR1, but can also be stimulated in a T cell receptor (TCR)-independent manner by pro-inflammatory cytokines. Therefore, their role in both sterile and non-sterile diseases are of great interest and only just beginning to be explored. To understand the role of MAIT cells in non-sterile inflammation, we utilized a controlled human infection model of live Salmonella enterica serovar Paratyphi A. We observed that at the time of diagnosis MAIT cells had an activated phenotype, which was maintained even after antibiotic treatment. We analysed the TCR repertoire of MAIT cells in diagnosed individuals to determine if the MAIT cell response to infection was antigen- driven. We found that infection led to redistribution of the repertoire, with transient contraction of the over-represented clones at the peak of infection. To understand the role of MAIT cells in sterile inflammation we examined cancer sections and found that MAIT cells infiltrate tumours derived from various tissues and that the source of MAIT cells was from tissue-resident MAIT cell subsets. We also determined that MAIT cells may respond to BCG immunotherapy of bladder cancer, as they are both present and activated in the bladder following treatment. Finally, we wanted to determine the extent to which both the TCRα and TCRβ usage affected MAIT cell responses. We found that the TRAJ usage, which relatively defines circulating versus tissue-resident MAIT subsets, has a large impact on the MAIT TCR response to both bacterial and ligand stimulation. We also investigated selected TCRβ clonotypes identified in Salmonella-infected individuals and found that the MAIT cell clonotypes that expanded after infection had stronger TCR-dependent activation than did contracted clonotypes from the same individual. In conclusion, we have characterised the function and phenotype of MAIT cells in human infection, cancer and cancer immunotherapy as well as provide insight into the usage and importance of the specific MAIT cells TCRα and TCRβ chains.